2014
DOI: 10.1080/19345747.2014.946634
|View full text |Cite|
|
Sign up to set email alerts
|

A Random Assignment Evaluation of Learning Communities at Kingsborough Community College—Seven Years Later

Abstract: Community colleges play a vital role in higher education, enrolling more than one in every three postsecondary students. While their market share has grown over the past 50 years, students' success rates remain low. Consequently, community college stakeholders are searching with mounting urgency for strategies that increase rates of success. We evaluate the effects of one such strategy, learning communities, from a randomized trial of over 1,500 students at a large urban college in the City University of New Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Portions of this article (in particular, the Introduction and background sections titled "Learning Communities," "Why Learning Communities Are Expected to Work," and "Evidence of the Effectiveness of Learning Communities") are similar or identical to a recently published article sharing the same lead author: Weiss, Mayer, et al (2014). Portions of this article (in particular, the Introduction and background sections titled "Learning Communities," "Why Learning Communities Are Expected to Work," and "Evidence of the Effectiveness of Learning Communities") are similar or identical to a recently published article sharing the same lead author: Weiss, Mayer, et al (2014).…”
Section: Appendixmentioning
confidence: 85%
“…Portions of this article (in particular, the Introduction and background sections titled "Learning Communities," "Why Learning Communities Are Expected to Work," and "Evidence of the Effectiveness of Learning Communities") are similar or identical to a recently published article sharing the same lead author: Weiss, Mayer, et al (2014). Portions of this article (in particular, the Introduction and background sections titled "Learning Communities," "Why Learning Communities Are Expected to Work," and "Evidence of the Effectiveness of Learning Communities") are similar or identical to a recently published article sharing the same lead author: Weiss, Mayer, et al (2014).…”
Section: Appendixmentioning
confidence: 85%
“…In a study of six learning communities conducted by the National Center for Postsecondary Research, one learning community created social relationships via linked courses but also helped students gain college know‐how via enhanced advising and a student success course and made college life more feasible via textbook vouchers. The impact of participation on progression toward a degree was larger at this site than at others in the study (Visher et al., ); subsequent follow‐up research found that the positive impact on credit accrual was sustained for up to 7 years (Weiss et al., ).…”
Section: Holistic Nonacademic Supportmentioning
confidence: 98%
“… § Sources : Bers & Younger, ; CCCSE, ; Cho & Karp, ; Crisp, ; Crisp & Taggart, ; Hatch & Bohlig, ; Jaggars, Hodara, Cho, & Xu, ; Karp, Raufman, Efthimiou, & Ritze, ; Kuh, ; Melguizo, Kienzl, & Kosiewicz, ; Mitchell, Alozie, & Wathington, ; Taggart & Crisp, ; Weiss et al., .…”
Section: Key Dimensions Of High‐impact and Promising Practicesmentioning
confidence: 99%